Mapping Atomic Hydrogen in the Disk of the Milky Way - Hiep, Nguyen Van; Anh, Pham Tuan; Darriulat, Pierre; Diep, Pham Ngoc; Dong, Pham Ngoc; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Thao, Nguyen Thi (Communications in Physics, 2013)
The VATLY radio telescope has been used to draw the map of atomic hydrogen gas in the disk of the Milky Way. Evidence has been obtained for its differential rotation, its cloud and arm structure and the presence of a dark matter halo.